Determination of azithromycin residue in pork using a molecularly imprinted monolithic microcolumn coupled to liquid chromatography with tandem mass spectrometry. Issue 7 (11th March 2016) - Zhou, Tong; Yang, Haicui; Jin, Zhen; Liu, Qingying; Song, Xuqin; He, Limin; Fang, Binghu; Meng, Chenying
Abstract : Using spiramycin as a dummy template, a molecularly imprinted polymer monolithic micro‐column with high selection to azithromycin was prepared in a micropipette tip. The imprinting factor of the monolithic micro‐column prepared was approximately 2.67 and the morphological structure of the polymers was characterized by scanning electron microscopy. A simple, sensitive, and reproducible method based on the imprinted monolithic micro‐column coupled to liquid chromatography with tandem mass spectrometry was developed for determining the residues of azithromycin in pork. Pork samples were extracted with acetonitrile, cleaned up under the optimal monolithic micro‐column conditions, and analyzed using liquid chromatography with tandem mass spectrometry in the multiple reaction monitoring mode. The assay exhibited a linear dynamic range of 0.50–50 μg/L with the correlation coefficient ( r 2 ) above 0.99. In the three spiking levels of 0.50, 1.0, and 10 μg/kg, the average recoveries of azithromycin from pork samples were between 85.8 and 96.5% with a relative standard deviation below 10%. The limit of detection and limit of quantitation were 0.03 and 0.1 μg/kg, respectively.